Studies on Mollusca of Saurashtra Coast-II (Pelecypoda) - Sarvaiya, R. T. (Fishery Technology, 1977)
The paper deals with the proximate composition of Crassostrea graplzoides, C. cucullata, Placenta placenta, Pinna vexillum, P. bicolor, P. atropurpurea, Solen truncatus and Pitar erycina. Seasonal variations in water, protein, salt and ash in the meat of C. graphoides, C. cucullata and P. placenta are reported. Percentage of meat is high in S. truncatus and low in C. graphoides, C. cucullata and P. erycina. Most of these species contain higher moisture than gastropods.